2021
DOI: 10.3389/fphar.2021.722638
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Histone Deacetylase 6 for Interleukin-6 Induced Epithelial-Mesenchymal Transition, Proliferation, and Migration of Peritoneal Mesothelial Cells

Abstract: Aims: Influenced by microenvironment, human peritoneal mesothelial cells (HPMCs) acquired fibrotic phenotype, which was identified as the protagonist for peritoneal fibrosis. In this study, we examined the role of histone deacetylase 6 (HDAC6) for interleukin-6 (IL-6) induced epithelial-mesenchymal transition (EMT), proliferation, and migration of HPMCs.Methods: The role of HDAC6 in IL-6-elicited EMT of HPMCs was tested by morphological observation of light microscope, immunoblotting, and immune-fluorescence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…In our previous study, we found an elevated expression of HDAC6 in peritoneum and dialysis effluent from PD patients ( 29 ). Moreover, we demonstrated that HDAC6 was indispensable in interleukin-6 induced EMT, proliferation and migration of peritoneal mesothelial cells ( 30 ). However, the link between HDAC6 and M2 polarization in PF remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we found an elevated expression of HDAC6 in peritoneum and dialysis effluent from PD patients ( 29 ). Moreover, we demonstrated that HDAC6 was indispensable in interleukin-6 induced EMT, proliferation and migration of peritoneal mesothelial cells ( 30 ). However, the link between HDAC6 and M2 polarization in PF remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…EMT is an important mechanism for migration and wound healing that can promote tumor progression ( 27 ). HDAC6 inhibition is proved to upregulate E-cadherin, a marker of EMT, making breast cancer cells or peritoneal mesothelial cells less susceptible to undergoing EMT ( 12 ). HDAC6 abrogation also reversed TGF-β-mediated EMT in breast cancer cells ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, HDAC6 is highly expressed in estrogen receptor-positive breast cancer cells and accelerates the metastatic process of breast cancer by reducing the acetylation modification of α-tubulin, enhancing microtubule activity, and promoting cell adhesion and migration ( 9 , 11 ). In leukemia cells, HDAC6 inhibitors can inhibit the process of α-tubulin deacetylation by HDAC6, disrupting the microtubule dynamics system and ultimately inhibiting cancer cell migration ( 12 ). Furthermore, HDAC6 inhibition can block the process of proliferation and invasion of gastric cancer cells ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study illustrated the mechanism of IL-6-induced EMT from an epigenetic standpoint. The authors found that exposing human peritoneal mesothelial cells to IL-6 increased the expression of histone deacetylase 6, which not only regulated IL-6 downstream of JAK2/STAT3 signaling but also activated TGF-β/Smad3 signaling, resulting in a change in the phenotype and increased cell migration 65 .…”
Section: The Role Of Il-6 In Fibrosis In Various Tissuesmentioning
confidence: 99%